Impact of the Elimination of the National Health Insurance (BPJS Health) Service Classes on Access and Quality of Healthcare in Indoneseia: A Systematic Review - Daniel Pradana Andrian Wicaksono (Universitas Airlangga, 2025)
This study aims to analyze the impact of eliminating BPJS Health classes and implementing the Standard Inpatient Class (KRIS) in Indonesia, focusing on healthcare access, service quality, financial sustainability, and governance. The policy was introduced to promote social equity and reduce disparities in healthcare delivery. A systematic literature review was conducted using databases such as Google Scholar, PubMed, and Scopus, covering studies published between 2019 and 2024. The selected literature met inclusion and exclusion criteria to ensure relevance and quality, and a narrative synthesis was applied to identify major patterns and policy implications.The findings indicate that KRIS can improve fairness in healthcare access and simplify administrative processes. However, significant challenges remain, especially regarding hospital preparedness in less developed regions, where overcrowding, longer waiting times, and potential declines in service quality are likely to occur. The transition from a classbased system to a standardized model also raises financial concerns, particularly about sustainability and equity in funding. In addition, governance weaknesses and limited policy communication have led to uncertainty and public hesitation.Overall, KRIS reflects a progressive step toward healthcare equity but demands careful implementation. Sustainable financing, improved hospital capacity, effective governance, and active public participation are essential for ensuring its success. Future studies should continue exploring financial mechanisms and regional readiness to guide more inclusive and sustainable policy development.